Altmetrics in Practice - Buettgen, Stephan (Septentrio Conference Series, 2014)
>> See video of presentation (26 min.) Citation counts have long been the standard measure of academic research usage and impact. Specifically, published articles in prominent journals citing other published articles in other prominent journals equate to prestige and tenure. Metrics can now be harvested and applied to research around usage, captures, mentions, and social media, in addition to citations, giving a much more comprehensive and holistic view of impact. These new metrics are also much more timely than citation metrics and can keep pace with new formats much faster than the entrenched, legacy practices. In this session, we will highlight some practical ways institutions are using these new metrics today and what the future holds.